2016
DOI: 10.1002/nvsm.1553
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring but not targeting: a critical analysis of “the Meth Project” aimed at Hispanic youth

Abstract: • This paper examines the Meth Project, a social marketing campaign that enlists violence and fear to persuade Anglo and Hispanic youth in the USA to avoid methamphetamines. Violent and graphic media spots, although perhaps initially effective for facilitating message acceptance, may be counterproductive for long-term campaign objectives. We draw on Witte's Extended Parallel Process Model to conceptualize how fear, risk, and behavior drive health-related behaviors. Merely translating the Anglo spots into Spani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Our findings illustrate that CEPS encourages consumer participation in viscerally shocking experiential campaigns, if congruent with the hedonic consumption experience being marketed. Therefore, CEPS is a distinct emotional response to those aroused by social marketing (Scarpaci and Burke 2016;Tannenbaum et al 2015;Cronin and Hopkinson 2017), as it seeks to encourage rather than prevent consumer participation, and is clear in its commercial and hedonic orientation. Another CEPS dimension is its ephemerality, leading to positive ethical judgement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings illustrate that CEPS encourages consumer participation in viscerally shocking experiential campaigns, if congruent with the hedonic consumption experience being marketed. Therefore, CEPS is a distinct emotional response to those aroused by social marketing (Scarpaci and Burke 2016;Tannenbaum et al 2015;Cronin and Hopkinson 2017), as it seeks to encourage rather than prevent consumer participation, and is clear in its commercial and hedonic orientation. Another CEPS dimension is its ephemerality, leading to positive ethical judgement.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive threat can "alienate consumers" (Urwin and Venter 2014, p. 203), resulting in undesirable beliefs about experiential campaigns. These beliefs may work to the detriment of the brand (Hsieh et al 2012;Moore 2015), or the social marketing campaign (Scarpaci and Burke 2016). Positively valenced adverts are often posed as eliciting stronger, longer-lasting attitudes (Eckler and Bolls 2011).…”
Section: Threat-based Experiential Marketing Communicationsmentioning
confidence: 99%
“…Some research in the PSA space advocates the use of fear appeals (Bleakley et al, 2015;Manno et al, 2018;Nan, 2017). However, other research, such as that of Scarpaci and Burke (2016), found that fear appeals backfire. Bleakley et al (2015) used adolescents as subjects in PSAs for reducing sugar sweetened beverages like Coke.…”
Section: Divergent Findings In the Use Of Fear Appealsmentioning
confidence: 99%
“…Excessive threat can "alienate consumers" (Urwin and Venter, 2014, p. 203), resulting in undesirable beliefs about experiential campaigns. These beliefs may work to the detriment of the brand (Hsieh et al, 2012;Moore, 2015), or the social marketing campaign (Scarpaci and Burke, 2016). Positively valenced adverts are often posed as eliciting stronger, longerlasting attitudes (Eckler and Bolls, 2011).…”
Section: Threat-based Experiential Marketing Communicationsmentioning
confidence: 99%